Halal tourism: the approach to central java’s tourism destinations development by mean of entrepreneur orientation - Ratih Pratiwi; Sofwan Baharrudin; Sapta Yulinar Maulidya; Retno Kusumaningrum (Universitas Merdeka Malang, 2022)
This study aims to analyze and explain the effect of entrepreneurial orientation (innovation and risk-taking) in encouraging the implementation of halal tourism. The predicted results suggest that this research will be useful in the development of Indonesian halal tourist destinations, as well as a starting point for future studies. The Central Java region is the location of this explanatory research. There are 516 tourist sites in Central Java that are included in this survey. In this study, 120 ODTWs from various regions in Central Java participated. To analyze the data collected from the questionnaires, a statistical approach known as Sem PLS was used. The Likert scale ranges from 1 to 5. The results of the analysis show that innovation and risk-taking have a significant positive effect on competitive advantage. innovation does not have a significant positive effect on the implementation of halal tourism but risk-taking has a significant positive effect on the implementation of halal tourism. The implementation of halal tourism has a significant effect on competitive advantage. The competitive advantage of tourist destinations can be built from innovation and the ability to take risks.